Initial value problems for integro-differential equations of Volterra type in Banach spaces. (1994) - Guo, Dajun
Abstract : This paper investigates the extremal solutions of initial value problems for first order integro-differential equations of Volterra type in Banach spaces by means of establishing a comparison result.